Anísio Teixeira’s Legacy to Brazilian Education - Nunes, Clarice (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
An Analysis of the work of Anísio Teixeira (1900-1971), based on research in his archives that permitted a questioning of the current interpretations found in the pedagogical literature between 1970 and 1990. The focus is on his role as administrator at the secretaries of education of Rio de Janeiro (1930-1935) and Salvador (1940-1950), as coordinator of public organs, particularly the Instituto Nacional de Pesquisas Educacionais/INEP (1952–1964). His legacy was built amid political-ideological clashes due to his stance in defense of democracy and education for democracy, both in his administrative work and publications. The controversy surrounding the book Educação não é Privilégio (1957) and its nationwide repercussion are examined. Anísio Teixeira and his collaborators built a domain of identification and practice for professional educators, defining the career and producing policy aimed at creating a school system from elementary education to university.